Nano graphite super lubricant and preparation method thereof
By scientifically proportioning components such as nano-graphite, natural polymer additives, MOFs, and hyperbranched polymers, a high-efficiency lubricating film is formed, which solves the problem of insufficient performance of traditional lubricants under high precision, high load, and extreme working conditions. It achieves a dual breakthrough in lubrication performance and environmental protection, adapts to a wide temperature range, and extends equipment life.
Patent Information
- Application Number
- CN202511224219.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-11-14
AI Technical Summary
Traditional lubricants are inadequate in high-precision, high-load, and extreme working conditions. They have poor wear resistance, extreme pressure carrying capacity, and thermal stability, as well as insufficient environmental friendliness. Furthermore, they have limited functionality, cannot dynamically adapt to changes in working conditions, and fail to fully tap the synergistic potential between components.
It uses a scientifically formulated blend of nano-graphite, natural polymer additives, MOFs, hyperbranched polymers, and biodegradable plasticizers to form a highly efficient lubricating film, enhancing extreme pressure load capacity, adapting to a wide temperature range, and ensuring environmental friendliness.
It significantly reduces friction and wear, improves lubrication performance and stability, meets the dual requirements of high performance and environmental protection, extends equipment service life, and reduces energy consumption and maintenance costs.
Smart Images

Figure CN120944613A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lubricant technology, specifically to a nano-graphite super lubricant and its preparation method. Background Technology
[0002] As industrial machinery develops towards higher precision, higher loads, and extreme operating conditions, traditional lubricants face severe challenges in terms of performance improvement and environmental friendliness. The operating efficiency, lifespan, and energy consumption of mechanical equipment are directly affected by the performance of lubricants. Especially in heavy-load, high-speed, or high-temperature environments, the wear resistance, extreme pressure bearing capacity, and thermal stability of lubricants have become key technical bottlenecks. At the same time, global attention to energy conservation, emission reduction, and sustainable development is driving the green transformation of lubricating materials. Biodegradable components, low volatile organic compounds (VOCs), and resource recycling have become the focus of industry research and development. Breakthroughs in nanotechnology, polymer materials science, and metal-organic frameworks (MOFs) have provided a technological foundation for developing new lubricants that combine high performance and environmental protection, prompting the industry to explore ways to achieve a leapfrog improvement in lubrication performance through component synergy.
[0003] Traditional lubricants mainly rely on mineral oil or simple additive combinations, which have several drawbacks: First, their lubrication performance is limited. The poor dispersibility of base oil and additives makes it difficult to form a stable lubricating film, resulting in a high coefficient of friction and increased wear, especially prone to failure under extreme pressure or temperature. Second, they are not environmentally friendly. Most products contain non-degradable components, which can pollute soil and water bodies after leakage, and the production process also results in excessive emissions of volatile organic compounds. Third, they have limited functionality. Traditional additives have independent mechanisms of action and cannot dynamically adapt to changes in operating conditions. For example, their viscosity drops sharply at high temperatures and their fluidity is poor at low temperatures, leading to frequent equipment maintenance and increased energy consumption. In addition, traditional technologies lack a systematic approach to the design of nanomaterials and polymer structures, failing to fully explore the synergistic potential between components and limiting further improvements in lubricant performance. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a nano-graphite super lubricant and its preparation method. By scientifically proportioning base oil, nano-graphite, natural polymer additives, MOFs, hyperbranched polymers, and biodegradable plasticizers, a dual breakthrough in lubrication performance and environmental friendliness is achieved. This lubricant utilizes the layered structure of nano-graphite and the synergistic effect of polymers to form a highly efficient lubricating film, significantly reducing friction and wear. MOF materials enhance extreme pressure bearing capacity, and hyperbranched polymers optimize viscosity-temperature properties, adapting to a wide temperature range of -30℃ to 200℃.
[0005] To solve the above-mentioned technical problems, the present invention provides the following technical solution: In one aspect, a nano-graphite super lubricant, comprising the following components by weight:
[0006] Base oil: 50-80 parts;
[0007] Nano-graphite: 5-15 parts;
[0008] Natural polymer additives: 2-8 parts;
[0009] Nanoscale metal-organic framework (MOF) materials: 1-5 parts;
[0010] Hyperbranched polymer: 3-10 parts;
[0011] Biodegradable fatty acid ester plasticizers: 2-6 parts.
[0012] Furthermore, the natural polymer additive is chitosan, which has a molecular weight of 50,000-200,000 Da. After being pulverized through a 150-mesh sieve, it is dried in a vacuum drying oven at 70°C for 3 hours, and the moisture content after drying is ≤1%.
[0013] Furthermore, the nanoscale metal-organic framework (MOF) material is ZIF-8, with a particle size of 50-200 nm and a pore size of 0.5-1.2 nm. After vacuum activation, the pore volume is 0.6-1.0 cm³. 3 / g.
[0014] Furthermore, the hyperbranched polymer is selected from hyperbranched polyester and hyperbranched polyether; the number-average molecular weight of the hyperbranched polyester and hyperbranched polyether is 3000-10000 g / mol, and the content of terminal hydroxyl groups in the molecular chain is 5-10 mmol / g.
[0015] Furthermore, the biodegradable fatty acid ester plasticizer is ethyl palmitate, wherein the ethyl palmitate has a purity ≥98%, an acid value ≤0.5mgKOH / g, and a moisture content ≤0.05%.
[0016] Furthermore, the base oil is a mineral oil or a synthetic oil, wherein the mineral oil is a paraffinic mineral oil with a kinematic viscosity of 50-150 mmHg at 40°C. 2 / s; The synthetic oil is a polyalpha-olefin oil with a kinematic viscosity of 40-120 mm at 40°C. 2 / s.
[0017] On the other hand, a method for preparing a nano-graphite super lubricant includes the following steps:
[0018] S100, Raw material pretreatment and weighing: Base oil, nano-graphite, natural polymer additives, MOFs, hyperbranched polymers, and biodegradable fatty acid ester plasticizers are pretreated separately, and then each pretreated component is accurately weighed according to the weight parts.
[0019] S200, Nanographite and Natural Polymer Additive Coating: The pretreated nanographite and natural polymer additives are added to a dispersion tank and ultrasonically dispersed at 300W power for 30 minutes at 40℃.
[0020] S300, Dispersion of base oil and plasticizer: Add base oil and biodegradable fatty acid ester plasticizer to the coating product obtained from the coating step of nano-graphite and natural polymer additives, heat to 50°C, and stir at 600 r / min for 30-45 min.
[0021] S400, Combination of hyperbranched polymers and MOFs: Hyperbranched polymers and nanoscale metal-organic framework materials (MOFs) are added to the mixture obtained from the base oil and plasticizer dispersion step, the temperature is raised to 70°C, and ultrasonic treatment is performed at 500W power for 20 minutes.
[0022] S500, system fusion and finished product preparation: After ultrasonic treatment, maintain the temperature at 70℃ and continue stirring at a speed of 600-800r / min for 30min. After naturally cooling to room temperature, nano-graphite super lubricant is obtained.
[0023] Furthermore, in the S100 raw material pretreatment and weighing process, the pretreatment of each component is as follows: the base oil is mineral oil, which is filtered through a plate and frame filter after standing sedimentation for 48 hours, with a filter cloth pore size of 5μm; the synthetic oil is vacuum dehydrated for 2 hours at 80℃ and a vacuum degree of 0.09MPa; the nano-graphite is surface modified with silane coupling agent KH-550, mixed at a mass ratio of 100:5-8 of nano-graphite to silane coupling agent, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, and then dried in a vacuum drying oven at 80℃ for 3 hours; the chitosan is pulverized and... The MOFs were dried for 3 hours at 70℃ and 0.08MPa vacuum through a 50-mesh sieve. The MOFs were washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20, centrifuged at 3500 r / min for 10 minutes each time, and activated in a vacuum drying oven at 110℃ for 7 hours. The hyperbranched polymer was heated to 50-80℃ to melt, filtered under pressure through a 0.22μm polytetrafluoroethylene filter membrane, and degassed for 1.5 hours at 70℃ and 0.09MPa vacuum. The biodegradable fatty acid ester plasticizers were distilled under reduced pressure at 0.085MPa and 80℃, discarding 10% of the fore- and post-distillate fractions and collecting the middle fraction.
[0024] Furthermore, in the S300 process, the weight ratio of the added base oil to the biodegradable fatty acid ester plasticizer is 25:1-40:3. During the stirring process, samples are taken every 15 minutes for observation until the system is uniformly transparent or semi-transparent.
[0025] Furthermore, in the S400, the mass ratio of the hyperbranched polymer to the nanoscale metal-organic framework material MOFs is 3:1-10:1, and the distance between the ultrasonic probe and the liquid surface of the material during ultrasonic treatment is 2-5cm.
[0026] Compared with existing technologies, this nano-graphite super lubricant and its preparation method have the following beneficial effects:
[0027] I. This invention improves lubrication performance and stability by scientifically proportioning base oil, nano-graphite, natural polymer additives, and hyperbranched polymer components. Utilizing the layered structure of nano-graphite and the synergistic effect of natural polymer additives, a highly efficient lubricating film is formed, effectively reducing the coefficient of friction and enhancing wear resistance. Furthermore, the introduction of hyperbranched polymers optimizes the viscosity index of the lubricant, enabling it to maintain excellent lubrication performance at different temperatures, extending equipment lifespan, and reducing energy consumption and maintenance costs.
[0028] II. This invention combines nanoscale metal-organic framework materials (MOFs) with biodegradable fatty acid ester plasticizers, which not only improves the extreme pressure performance and load-bearing capacity of lubricants but also ensures the environmental friendliness of the product. The porous structure of MOFs effectively adsorbs and stores lubricating oil, releasing it under extreme operating conditions to form dynamic lubrication protection. The addition of biodegradable plasticizers reduces the environmental pollution caused by traditional lubricants. This green and efficient lubrication design meets the dual needs of modern industry for sustainable development and high-performance lubrication, and promotes the advancement of lubrication technology.
[0029] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.
[0031] Figure 1 This is a flowchart of a method for preparing nano-graphite super lubricant. Detailed Implementation
[0032] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.
[0033] Example 1:
[0034] Implementation of nano-graphite super lubricant in high-speed motor bearing lubrication.
[0035] Raw material pretreatment and weighing:
[0036] Select a kinematic viscosity of 80 mmHg at 40℃. 2 Using polyalphaolefin oil as the base oil, the oil is vacuum dehydrated for 2 hours at 80°C and 0.09 MPa to remove water and prevent air bubbles from forming during subsequent mixing. 60 parts of the pretreated base oil are accurately weighed, which can provide a basic lubricating carrier for the lubricant and ensure the fluidity of the lubrication system.
[0037] Nanographite and silane coupling agent KH-550 were mixed at a mass ratio of 100:7 and stirred in a constant temperature water bath at 55℃ for 1.5 hours. The surface properties of nanographite were optimized by the action of silane coupling agent, and its compatibility with other components was enhanced. Then, the mixture was centrifuged at 4000 r / min for 15 minutes to remove unreacted coupling agent, and then dried in a vacuum drying oven at 80℃ for 3 hours. Eight portions of pretreated nanographite were accurately weighed. The layered structure can reduce the direct contact between friction surfaces.
[0038] Chitosan with a molecular weight of 80,000 Da was selected, pulverized, and passed through a 150-mesh sieve to ensure particle uniformity. It was dried at 70℃ and a vacuum of 0.08 MPa for 3 hours, resulting in a moisture content of 0.6% after drying, which reduced the impact of moisture on the stability of the system. Three portions of the pretreated chitosan were accurately weighed, and the polar groups on its molecular chain can combine with the surface of nano-graphite to improve the dispersion effect.
[0039] ZIF-8 particles with a particle size of 100 nm and a pore size of 0.7 nm were selected and washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20, centrifuged at 3500 r / min for 10 minutes each time to remove surface impurities. The particles were then activated in a vacuum drying oven at 110℃ for 7 hours, resulting in a pore volume of 0.7 cm³. 3 / g, which is beneficial for subsequent adsorption and stabilization of other components. Accurately weigh two portions of pretreated ZIF-8.
[0040] Hyperbranched polyether with a number average molecular weight of 5000 g / mol and a terminal hydroxyl content of 6 mmol / g was selected. After melting at 60°C, it was filtered under pressure through a 0.22 μm polytetrafluoroethylene filter membrane to remove mechanical impurities. Then, it was degassed at 70°C and a vacuum of 0.09 MPa for 1.5 hours to avoid bubbles affecting the homogeneity of the system. Five portions of the pretreated hyperbranched polyether were accurately weighed. Its branched structure can enhance the viscosity-temperature properties of the lubricant.
[0041] Ethyl palmitate (purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%) was selected and distilled under reduced pressure at 0.085 MPa and 80 °C. 10% of the fore-distillate and 10% of the back-distillate were discarded, and the middle fraction was collected to improve the purity. Three portions of the pretreated ethyl palmitate were accurately weighed, which can improve the low-temperature fluidity of the system.
[0042] Nano-graphite coated with natural polymer additives:
[0043] Eight parts of pretreated nano-graphite and three parts of chitosan were added to a dispersion tank and ultrasonically dispersed at 300W power at 40℃ for 30 minutes. The high-frequency vibration of the ultrasound caused the chitosan to be uniformly coated on the surface of the nano-graphite, reducing the aggregation of nano-graphite particles and forming a stable coating system.
[0044] Dispersion of base oil and plasticizer:
[0045] Add 60 parts of base oil and 3 parts of ethyl palmitate (base oil to plasticizer weight ratio of 20:1) to the above-mentioned coated product, heat to 50°C, and stir at 600 r / min for 35 minutes. Take a sample every 15 minutes during the stirring process. The final system is semi-transparent. At this time, the base oil acts as a continuous phase to uniformly disperse the coated product and plasticizer. The plasticizer can be incorporated into the system to adjust the viscosity.
[0046] Combination of hyperbranched polymers with MOFs:
[0047] Add 5 parts hyperbranched polyether and 2 parts ZIF-8 (hyperbranched polymer to MOFs mass ratio of 2.5:1) to the above mixture, heat to 70°C, and sonicate at 500W power for 20 minutes. The distance between the ultrasonic probe and the liquid surface of the material is 3cm. The ultrasonic action promotes the interaction between the hyperbranched polymer and MOFs, forming a stable composite structure and enhancing the load-carrying capacity of the lubricant.
[0048] System integration and finished product preparation:
[0049] After ultrasonic treatment, maintain the temperature at 70℃ and continue stirring at 700r / min for 30 minutes to fully integrate the components and form a homogeneous system. After naturally cooling to room temperature, a nano-graphite super lubricant suitable for high-speed motor bearings is obtained.
[0050] Quality assessment data:
[0051] The kinematic viscosity of this lubricant is 95 mmHg at 40°C. 2 After 500 hours of continuous operation in a high-speed motor bearing at a speed of 3000 r / min, the bearing wear was only 0.002 mm, and the coefficient of friction remained stable at 0.035, demonstrating good lubrication performance and stability.
[0052] In summary, this embodiment addresses the lubrication needs of high-speed motor bearings by preparing a nano-graphite super lubricant. The process involves precise weighing and pretreatment of polyalphaolefin oil, nano-graphite, chitosan, ZIF-8, hyperbranched polyether, and ethyl palmitate according to a specific process. Following steps such as nano-graphite and chitosan coating, base oil and plasticizer dispersion, hyperbranched polymer and ZIF-8 bonding, and system fusion, the lubricant is produced. Figure 1 As shown, the target lubricant was prepared, which has a kinematic viscosity of 95 mmHg at 40°C. 2 After 500 hours of continuous operation in a high-speed motor bearing at 3000 r / min, the bearing wear was only 0.002 mm, and the coefficient of friction remained stable at 0.035. This fully demonstrates the excellent lubrication performance and stability under the synergistic effect of the components, making it suitable for high-speed motor bearing lubrication scenarios.
[0053] Example 2:
[0054] Application of nano-graphite super lubricants with different amounts of ethyl palmitate in the lubrication of high-speed motor bearings.
[0055] Raw material pretreatment and weighing:
[0056] Base oil: Selected with a kinematic viscosity of 80 mmHg at 40°C. 2 The polyalphaolefin oil of / s was vacuum dehydrated at 80℃ and 0.09MPa for 2 hours, and 60 parts were accurately weighed.
[0057] Nanographite: Mixed with silane coupling agent KH-550 at a mass ratio of 100:7, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, vacuum dried at 80℃ for 3 hours, and accurately weighed into 8 portions.
[0058] Chitosan: molecular weight 80000 Da, pulverized through a 150-mesh sieve, dried at 70℃ and vacuum degree 0.08MPa for 3 hours (moisture content 0.6%), and accurately weighed in 3 portions.
[0059] ZIF-8: Particle size 100 nm, pore size 0.7 nm, washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20 (centrifuged at 3500 r / min for 10 minutes each time), and activated by vacuum drying at 110℃ for 7 hours (pore volume 0.7 cm³).3 Weigh two portions accurately (g).
[0060] Hyperbranched polyether: number average molecular weight 5000 g / mol, terminal hydroxyl content 6 mmol / g, melted at 60℃ and filtered through a 0.22 μm filter membrane, degassed at 70℃ and vacuum degree 0.09 MPa for 1.5 hours, and accurately weighed 5 portions.
[0061] Ethyl palmitate: purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%, distilled under reduced pressure at 0.085 MPa and 80℃ (discarding 10% of the initial and final fractions), and accurately weighed in portions of 2, 3, 4, 5, and 6 respectively.
[0062] Preparation steps (the steps are the same for all 5 experimental groups):
[0063] Nanographite and chitosan coating: Add 8 parts of nanographite and 3 parts of chitosan to a dispersion tank and ultrasonically disperse at 300W power for 30 minutes at 40℃.
[0064] Dispersion of base oil and plasticizer: Add 60 parts of base oil and the corresponding amount of ethyl palmitate (2-6 parts) to the coated product, heat to 50°C, and stir at 600 r / min for 35 minutes until it becomes translucent.
[0065] Combining hyperbranched polyether with ZIF-8: Add 5 parts hyperbranched polyether and 2 parts ZIF-8, heat to 70℃, and sonicate at 500W power for 20 minutes (probe 3cm from the liquid surface).
[0066] System integration and finished product: Stir at 700 r / min for 30 minutes at 70℃, and let cool naturally to room temperature to obtain 5 groups of lubricants.
[0067] Comparison table of the effects of ethyl palmitate on lubricant performance.
[0068]
[0069] In summary, within the range of 2-6 parts ethyl palmitate specified in this invention, it significantly optimizes the performance of the lubricant. As the dosage increases, the kinematic viscosity at 40°C gradually decreases, and the low-temperature fluidity improves (the viscosity change rate decreases at -30°C). When the dosage is 4 parts, the wear is minimal (0.0018 mm), the coefficient of friction is lowest (0.032), and the overall performance is optimal. This indicates that ethyl palmitate can balance the stability and fluidity of the lubricating film by adjusting the viscosity of the system, and its biodegradable properties enhance the environmental friendliness of the lubricant, meeting the high-efficiency and green lubrication requirements of industrial equipment in a wide temperature range.
[0070] Example 3:
[0071] Application of nano-graphite super lubricants with different ZIF-8 dosages in the lubrication of high-speed motor bearings.
[0072] Raw material pretreatment and weighing:
[0073] Base oil: Selected with a kinematic viscosity of 80 mmHg at 40°C. 2 The polyalphaolefin oil of / s was vacuum dehydrated at 80℃ and 0.09MPa for 2 hours, and 60 parts were accurately weighed.
[0074] Nanographite: Mixed with silane coupling agent KH-550 at a mass ratio of 100:7, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, vacuum dried at 80℃ for 3 hours, and accurately weighed into 8 portions.
[0075] Chitosan: molecular weight 80000 Da, pulverized through a 150-mesh sieve, dried at 70℃ and vacuum degree 0.08MPa for 3 hours (moisture content 0.6%), and accurately weighed in 3 portions.
[0076] ZIF-8: Particle size 100 nm, pore size 0.7 nm, washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20 (centrifuged at 3500 r / min for 10 minutes each time), and activated by vacuum drying at 110℃ for 7 hours (pore volume 0.7 cm³). 3 Weigh 1, 2, 3, 4 and 5 portions of each portion (g).
[0077] Hyperbranched polyether: number average molecular weight 5000 g / mol, terminal hydroxyl content 6 mmol / g, melted at 60℃ and filtered through a 0.22 μm filter membrane, degassed at 70℃ and vacuum degree 0.09 MPa for 1.5 hours, and accurately weighed 5 portions.
[0078] Ethyl palmitate: purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%, distilled under reduced pressure at 0.085 MPa and 80℃ (discarding 10% of the initial and final fractions), and accurately weighed in 3 portions.
[0079] Preparation steps (the steps are the same for all 5 experimental groups):
[0080] Nanographite and chitosan coating: Add 8 parts of nanographite and 3 parts of chitosan to a dispersion tank and ultrasonically disperse at 300W power for 30 minutes at 40℃.
[0081] Dispersion of base oil and plasticizer: Add 60 parts of base oil and 3 parts of ethyl palmitate to the coated product, heat to 50°C, and stir at 600 r / min for 35 minutes until it becomes translucent.
[0082] Combining hyperbranched polyether with ZIF-8: Add 5 parts hyperbranched polyether and the corresponding amount of ZIF-8 (1-5 parts), heat to 70℃, and sonicate at 500W power for 20 minutes (probe 3cm from the liquid surface).
[0083] System integration and finished product: Stir at 700 r / min for 30 minutes at 70℃, and let cool naturally to room temperature to obtain 5 groups of lubricants.
[0084] Comparison table of the effects of ZIF-8 on lubricant performance.
[0085]
[0086] In summary, within the dosage range of 1-5 parts ZIF-8 specified in this invention, its effect on improving lubricant performance is significant. The porous structure of ZIF-8 enhances the adsorption and storage capacity of lubricating oil. With increasing dosage, extreme pressure bearing capacity and high temperature stability are gradually optimized, while wear and friction coefficient decrease. The best overall performance is achieved at 3 parts (wear 0.0015mm, friction coefficient 0.031, extreme pressure bearing capacity 1120N). Performance fluctuates slightly after excessive dosage, but is still better than the low dosage group. This indicates that ZIF-8 can strengthen the lubricating film strength through synergistic effect, improve the equipment's resistance to extreme working conditions, and extend its service life, meeting the design requirements of high-performance lubricants.
[0087] Example 4:
[0088] Application of nano-graphite super lubricants with different amounts of hyperbranched polyether in the lubrication of high-speed motor bearings.
[0089] Raw material pretreatment and weighing:
[0090] Base oil: Selected with a kinematic viscosity of 80 mmHg at 40°C. 2 The polyalphaolefin oil of / s was vacuum dehydrated at 80℃ and 0.09MPa for 2 hours, and 60 parts were accurately weighed.
[0091] Nanographite: Mixed with silane coupling agent KH-550 at a mass ratio of 100:7, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, vacuum dried at 80℃ for 3 hours, and accurately weighed into 8 portions.
[0092] Chitosan: molecular weight 80000 Da, pulverized through a 150-mesh sieve, dried at 70℃ and vacuum degree 0.08MPa for 3 hours (moisture content 0.6%), and accurately weighed in 3 portions.
[0093] ZIF-8: Particle size 100 nm, pore size 0.7 nm, washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20 (centrifuged at 3500 r / min for 10 minutes each time), and activated by vacuum drying at 110℃ for 7 hours (pore volume 0.7 cm³).3 Weigh two portions accurately (g).
[0094] Hyperbranched polyether: number average molecular weight 5000 g / mol, terminal hydroxyl content 6 mmol / g, melted at 60℃ and filtered through a 0.22 μm filter membrane, degassed at 70℃ and vacuum degree 0.09 MPa for 1.5 hours, and accurately weighed 3, 5, 7, 9 and 10 parts respectively.
[0095] Ethyl palmitate: purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%, distilled under reduced pressure at 0.085 MPa and 80℃ (discarding 10% of the initial and final fractions), and accurately weighed in 3 portions.
[0096] Preparation steps (the steps are the same for all 5 experimental groups):
[0097] Nanographite and chitosan coating: Add 8 parts of nanographite and 3 parts of chitosan to a dispersion tank and ultrasonically disperse at 300W power for 30 minutes at 40℃.
[0098] Dispersion of base oil and plasticizer: Add 60 parts of base oil and 3 parts of ethyl palmitate to the coated product, heat to 50°C, and stir at 600 r / min for 35 minutes until it becomes translucent.
[0099] Combining hyperbranched polyether with ZIF-8: Add the corresponding amount of hyperbranched polyether (3-10 parts) and 2 parts of ZIF-8, heat to 70℃, and sonicate at 500W power for 20 minutes (probe 3cm from the liquid surface).
[0100] System integration and finished product: Stir at 700 r / min for 30 minutes at 70℃, and let cool naturally to room temperature to obtain 5 groups of lubricants.
[0101] Comparison table of the effects of hyperbranched polyethers on lubricant performance.
[0102]
[0103]
[0104] In summary, within the dosage range of 3-10 parts of hyperbranched polyether specified in this invention, its effect on optimizing lubricant performance is significant. The branched structure of the hyperbranched polyether can effectively increase the viscosity index and improve viscosity-temperature properties, enabling the lubricant to maintain stable lubrication performance at both high and low temperatures. With increasing dosage, the kinematic viscosity at 40℃ and 100℃ gradually increases, the viscosity index improves, and the wear and friction coefficient first decrease and then slightly increase, with the optimal overall performance at 7 parts (viscosity index 210, wear 0.0017 mm, friction coefficient 0.032). This indicates that hyperbranched polyether can enhance the stability of the lubricating film, extend equipment life, and meet the requirements of wide temperature range operating conditions by adjusting the viscosity balance of the system.
[0105] Example 5:
[0106] Application of hyperbranched polyester as a substitute for hyperbranched polyether in nano-graphite super lubricant for high-speed motor bearing lubrication.
[0107] Raw material pretreatment and weighing:
[0108] Base oil: Selected with a kinematic viscosity of 80 mmHg at 40°C. 2 The polyalphaolefin oil of / s was vacuum dehydrated at 80℃ and 0.09MPa for 2 hours, and 60 parts were accurately weighed.
[0109] Nanographite: Mixed with silane coupling agent KH-550 at a mass ratio of 100:7, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, vacuum dried at 80℃ for 3 hours, and accurately weighed into 8 portions.
[0110] Chitosan: molecular weight 80000 Da, pulverized through a 150-mesh sieve, dried at 70℃ and vacuum degree 0.08MPa for 3 hours (moisture content 0.6%), and accurately weighed in 3 portions.
[0111] ZIF-8: Particle size 100 nm, pore size 0.7 nm, washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20 (centrifuged at 3500 r / min for 10 minutes each time), and activated by vacuum drying at 110℃ for 7 hours (pore volume 0.7 cm³). 3 Weigh two portions accurately (g).
[0112] Hyperbranched polyester: number average molecular weight 5000 g / mol, molecular chain terminal hydroxyl content 6 mmol / g, heated to 60℃ to melt, then filtered under pressure through a 0.22 μm polytetrafluoroethylene filter membrane, degassed for 1.5 hours at 70℃ and vacuum degree 0.09 MPa, and accurately weighed 5 parts.
[0113] Ethyl palmitate: purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%, distilled under reduced pressure at 0.085 MPa and 80℃ (discarding 10% of the initial and final fractions), and accurately weighed in 3 portions.
[0114] Preparation steps:
[0115] Nanographite and chitosan coating: 8 parts of pretreated nanographite and 3 parts of chitosan were added to a dispersion tank and ultrasonically dispersed at 300W power at 40℃ for 30 minutes to make chitosan uniformly coat the surface of nanographite and reduce agglomeration.
[0116] Dispersion of base oil and plasticizer: Add 60 parts of base oil and 3 parts of ethyl palmitate to the above-mentioned coated product, heat to 50°C, stir at 600 r / min for 35 minutes, and take a sample to observe until the system is semi-transparent to ensure that the base oil and plasticizer are fully mixed.
[0117] Combining hyperbranched polyester with ZIF-8: Add 5 parts hyperbranched polyester and 2 parts ZIF-8 to the mixture, heat to 70℃, and sonicate at 500W power for 20 minutes (the distance between the ultrasonic probe and the liquid surface of the material is 3cm) to promote the interaction between hyperbranched polyester and ZIF-8.
[0118] System fusion and finished product preparation: After ultrasonic treatment, maintain the temperature at 70℃ and continue stirring at 700r / min for 30 minutes to ensure complete fusion of all components. After natural cooling to room temperature, nano-graphite super lubricant is obtained.
[0119] Performance comparison explanation.
[0120]
[0121]
[0122] As can be seen from the table above, hyperbranched polyester and hyperbranched polyether have the same effect in this invention: both can optimize the viscosity index of the lubricant through their own branched structure, ensuring stable lubrication performance at different temperatures; when working synergistically with other components, both can effectively reduce the coefficient of friction and bearing wear, and improve the stability of the lubricating film. Therefore, in this invention, hyperbranched polyester can completely replace hyperbranched polyether without affecting the core performance of the lubricant.
[0123] Example 6:
[0124] Stability testing of nano-graphite super lubricant.
[0125] Raw material pretreatment and weighing:
[0126] Base oil: Selected with a kinematic viscosity of 80 mmHg at 40°C. 2 The polyalphaolefin oil of / s was vacuum dehydrated at 80℃ and 0.09MPa for 2 hours, and 60 parts were accurately weighed.
[0127] Nanographite: Mixed with silane coupling agent KH-550 at a mass ratio of 100:7, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, vacuum dried at 80℃ for 3 hours, and accurately weighed into 8 portions.
[0128] Chitosan: molecular weight 80000 Da, pulverized through a 150-mesh sieve, dried at 70℃ and vacuum degree 0.08MPa for 3 hours (moisture content 0.6%), and accurately weighed in 3 portions.
[0129] ZIF-8: Particle size 100 nm, pore size 0.7 nm, washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20 (centrifuged at 3500 r / min for 10 minutes each time), and activated by vacuum drying at 110℃ for 7 hours (pore volume 0.7 cm³). 3 Weigh two portions accurately (g).
[0130] Hyperbranched polyether: number average molecular weight 5000 g / mol, terminal hydroxyl content 6 mmol / g, melted at 60℃ and filtered through a 0.22 μm filter membrane, degassed at 70℃ and vacuum degree 0.09 MPa for 1.5 hours, and accurately weighed 5 portions.
[0131] Ethyl palmitate: purity 99%, acid value 0.3 mg KOH / g, moisture content 0.03%, distilled under reduced pressure at 0.085 MPa and 80℃ (discarding 10% of the initial and final fractions), and accurately weighed in 3 portions.
[0132] Preparation steps (completely consistent with Example 1):
[0133] Nanographite and chitosan coating: Add 8 parts of nanographite and 3 parts of chitosan to a dispersion tank and ultrasonically disperse at 300W power for 30 minutes at 40℃.
[0134] Dispersion of base oil and plasticizer: Add 60 parts of base oil and 3 parts of ethyl palmitate to the coated product, heat to 50°C, and stir at 600 r / min for 35 minutes until it becomes translucent.
[0135] Combining hyperbranched polyether with ZIF-8: Add 5 parts hyperbranched polyether and 2 parts ZIF-8, heat to 70℃, and sonicate at 500W power for 20 minutes (probe 3cm from the liquid surface).
[0136] System integration and finished product: Stir at 700 r / min for 30 minutes at 70℃, and then naturally cool to room temperature to obtain nano-graphite super lubricant.
[0137] Stability testing methods:
[0138] The prepared lubricant was sealed in a transparent container and left to stand at room temperature (25°C). Samples were taken at 0 days (initial state), 30 days, 60 days, 90 days, and 180 days to test the following indicators:
[0139] Appearance: Observe whether there is layering, sedimentation, or discoloration;
[0140] Kinematic viscosity at 40℃: measured using a viscometer;
[0141] Coefficient of friction: determined by a friction and wear testing machine (speed 3000 r / min, load 50 N);
[0142] Dispersibility: After centrifugation acceleration test (centrifugation at 3000 r / min for 30 minutes), observe the stratification.
[0143] A table comparing the stability at different times.
[0144]
[0145]
[0146] In summary, the nano-graphite super lubricant of this invention exhibits excellent stability during a 180-day settling period. While its appearance gradually changes from transparent to translucent over time, no significant stratification or severe sedimentation occurs; the kinematic viscosity at 40°C only decreases from 95 mmHg. 2 / s decreased to 91mm 2 / s, the friction coefficient increased slightly from 0.035 to 0.038, and the change was within an acceptable range; the centrifugation test showed good dispersibility, with only slight sedimentation after 180 days, which could be restored to uniformity after stirring. This indicates that the components, through scientific proportioning and process combination, formed a stable system. The layered structure of nano-graphite, the coating effect of chitosan, and the viscosity regulating function of hyperbranched polyether jointly ensured the performance stability of the lubricant after long-term storage, meeting the long-term use requirements of industrial equipment.
[0147] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A nano-graphite super lubricant, characterized in that, This lubricant comprises the following components by weight: Base oil: 50-80 parts; Nano-graphite: 5-15 parts; Natural polymer additives: 2-8 parts; Nanoscale metal-organic framework (MOF) materials: 1-5 parts; Hyperbranched polymer: 3-10 parts; Biodegradable fatty acid ester plasticizers: 2-6 parts.
2. The nano-graphite super lubricant according to claim 1, characterized in that, The natural polymer additive is chitosan, with a molecular weight of 50,000-200,000 Da. After being pulverized and passed through a 150-mesh sieve, it is dried in a vacuum drying oven at 70°C for 3 hours, and the moisture content after drying is ≤1%.
3. The nano-graphite super lubricant according to claim 1, characterized in that, The nanoscale metal-organic framework (MOF) materials are ZIF-8, with a particle size of 50-200 nm and a pore size of 0.5-1.2 nm. After vacuum activation, the pore volume is 0.6-1.0 cm³. 3 / g.
4. The nano-graphite super lubricant according to claim 1, characterized in that, The hyperbranched polymer is selected from hyperbranched polyester and hyperbranched polyether; the number average molecular weight of the hyperbranched polyester and hyperbranched polyether is 3000-10000 g / mol, and the content of terminal hydroxyl groups of the molecular chain is 5-10 mmol / g.
5. The nano-graphite super lubricant according to claim 1, characterized in that, The biodegradable fatty acid ester plasticizer is ethyl palmitate, wherein the ethyl palmitate has a purity ≥98%, an acid value ≤0.5mgKOH / g, and a moisture content ≤0.05%.
6. The nano-graphite super lubricant according to claim 1, characterized in that, The base oil is a mineral oil or a synthetic oil, and the mineral oil is a paraffinic mineral oil with a kinematic viscosity of 50-150 mmHg at 40°C. 2 / s; The synthetic oil is a polyalphaolefin oil with a kinematic viscosity of 40-120 mm² / s at 40°C.
7. A method for preparing a nano-graphite super-energy lubricant, the method being used to prepare the nano-graphite super-energy lubricant according to any one of claims 1-6, characterized in that, The specific steps of this preparation method are as follows: S100, Raw material pretreatment and weighing: Base oil, nano-graphite, natural polymer additives, MOFs, hyperbranched polymers, and biodegradable fatty acid ester plasticizers are pretreated separately, and then each pretreated component is accurately weighed according to the weight parts. S200, Nanographite and Natural Polymer Additive Coating: The pretreated nanographite and natural polymer additives are added to a dispersion tank and ultrasonically dispersed at 300W power for 30 minutes at 40℃. S300, Dispersion of base oil and plasticizer: Add base oil and biodegradable fatty acid ester plasticizer to the coating product obtained from the coating step of nano-graphite and natural polymer additives, heat to 50°C, and stir at 600 r / min for 30-45 min. S400, Combination of hyperbranched polymers and MOFs: Hyperbranched polymers and nanoscale metal-organic framework materials (MOFs) are added to the mixture obtained from the base oil and plasticizer dispersion step, the temperature is raised to 70°C, and ultrasonic treatment is performed at 500W power for 20 minutes. S500, system fusion and finished product preparation: After ultrasonic treatment, maintain the temperature at 70℃ and continue stirring at a speed of 600-800r / min for 30min. After naturally cooling to room temperature, nano-graphite super lubricant is obtained.
8. The method for preparing a nano-graphite super lubricant according to claim 7, characterized in that, In the raw material pretreatment and weighing of S100, the pretreatment of each component is as follows: the base oil is mineral oil, which is filtered through a plate and frame filter after standing sedimentation for 48 hours, with a filter cloth pore size of 5μm; the synthetic oil is vacuum dehydrated for 2 hours at 80℃ and a vacuum degree of 0.09MPa; the nano-graphite is surface modified with silane coupling agent KH-550, mixed at a mass ratio of 100:5-8 of nano-graphite to silane coupling agent, stirred in a constant temperature water bath at 55℃ for 1.5 hours, centrifuged at 4000r / min for 15 minutes, and then dried in a vacuum drying oven at 80℃ for 3 hours; the chitosan is pulverized through a 150-mesh sieve. The MOFs were sieved and dried at 70℃ and 0.08MPa vacuum for 3 hours; the MOFs were washed three times with anhydrous ethanol at a solid-liquid ratio of 1:20, centrifuged at 3500 r / min for 10 minutes each time, and activated in a vacuum drying oven at 110℃ for 7 hours; the hyperbranched polymer was heated to 50-80℃ to melt, filtered under pressure through a 0.22μm polytetrafluoroethylene filter membrane, and degassed at 70℃ and 0.09MPa vacuum for 1.5 hours; the biodegradable fatty acid ester plasticizers were distilled under reduced pressure at 0.085MPa vacuum and 80℃, discarding 10% of the fore- and post-distillate fractions and collecting the middle fraction.
9. The method for preparing a nano-graphite super lubricant according to claim 7, characterized in that, In the S300, the weight ratio of the added base oil to the biodegradable fatty acid ester plasticizer is 25:1-40:
3. During the stirring process, samples are taken every 15 minutes for observation until the system is uniformly transparent or semi-transparent.
10. The method for preparing a nano-graphite super lubricant according to claim 7, characterized in that, In the S400, the hyperbranched polymer is combined with MOFs, the mass ratio of the hyperbranched polymer to the nanoscale metal-organic framework material MOFs is 3:1-10:1, and the distance between the ultrasonic probe and the liquid surface of the material during ultrasonic treatment is 2-5cm.
Citation Information
Patent Citations
Metal rod coarse drawing lubricant and preparation method thereof
CN103614209A
Ceramic-powder-containing graphite lubricant with good wear resistance
CN105273814A
Lubricating oil containing graphite additive
CN106221860A
Preparation method for metal organic framework modified graphene oxide lamellar structure composite membrane used for organic solvent nanofiltration
CN106582317A
Fluorinated graphene reinforced lubricating oil and preparation method thereof
CN108130178A